Pengaruh Motivasi, Kepemimpinan, Lingkungan Kerja Dan Kompensasi Terhadap Kompetensi Dan Kinerja Guru Tetap SLTA: Studi Di Yayasan Yohannes Gabriel Keuskupan Surabaya - Yustinus Budi Hermanto (BIP's JURNAL BISNIS PERSPEKTIF, 2013)
The objective of this research is (1)to analyze the contribution of indicator of each variable that is motivation, leadership, working environment, compensation, competency and teachers’ performance; (2)to test the effect of these variables, motivation, leadership, working environment and compensation towards competency; (3)to test the effect of these variables, motivation, leadership, working environment and compensation towards performance; (4) the effect of motivation, leadership, working environment and compensation towards performance through competency; and (5)to test the effect of competency towards teachers’ performance. This research uses quantitative approach. The samples are taken by using purposive sampling method. The total numbers of the respondents in this research are 151 full time/permanent high school teachers at Yayasan Yohannes Gabriel Keuskupan Surabaya and they are analyzed by using descriptive statistic. SEM or Structural Equation Modeling is used to test the proposed hypothesis. The research results showed that (1 )all the indicators give significant contribution to each variable; (2) motivation and compensation variables have significant influence towards teachers’ competency; (3)motivation and working environment variables have significant influence towards teachers’ performance but leadership has no significant influence towards competency and teachers’ performance; (4)motivation and compensation variables have significant influence towards performance through competency while leadership and working environment variables do not have significant influence towards performance through competency. In this case, competency is as intervening variable for motivation through performance and is as moderating variable for compensation through performance. (5)competency has significant influence towards performance. In other words, high motivation accompanied with compensation and high competency will drive teachers’ performance higher.